Tartary buckwheat FtF3′H1 as a metabolic branch switch to increase anthocyanin content in transgenic plant - Li, Chenglei; Yang, Jingjing; Yang, Kai; Wu, Huala; Chen, Hui; Wu, Qi; Zhao, Haixia (Frontiers in Plant Science, 2022)
Tartary buckwheat (TB) is a pseudocereal rich in flavonoids, mainly including flavonols and anthocyanins. The flavonoid 3′-hydroxylase (F3′H) is a key enzyme in flavonoid biosynthesis and is encoded by two copies in TB genome. However, its biological function and effects on flavonol and anthocyanin synthesis in TB have not been well validated yet. In this study, we cloned the full-length FtF3′H1 gene highly expressed in all tissues (compared with FtF3′H2) according to TB flowering transcriptome data. The corresponding FtF3′H1 protein contains 534 amino acids with the molecular properties of the typical plant F3′H and belongs to the CYP75B family. During the flowering stage, the FtF3′H1 expression was highest in flowers, and its expression pattern showed a significant and positive correlation with the total flavonoids (R2> 0.95). The overexpression of FtF3′H1 in Arabidopsis thaliana, N. tabacum and TB hairy roots resulted in a significant increase in anthocyanin contents (p< 0.05) but a decrease in rutin (p< 0.05). The average anthocyanin contents were 2.94 mg/g (fresh weight, FW) in A. thaliana (about 135% increase), 1.18 mg/g (FW) in tobacco (about 17% increase), and 1.56 mg/g (FW) TB hairy roots (about 44% increase), and the rutin contents were dropped to about 53.85%, 14.99%, 46.31%, respectively. However, the expression of genes involved in anthocyanin (DFRs and ANSs) and flavonol (FLSs) synthesis pathways were significantly upregulated (p< 0.05). In particular, the expression level of DFR, a key enzyme that enters the anthocyanin branch, was upregulated thousand-fold in A. thaliana and in N. tabacum. These results might be attributed to FtF3′H1 protein with a higher substrate preference for anthocyanin synthesis substrates. Altogether, we identified the basic biochemical activity of FtF3′H1 in vivo and investigated its involvement in anthocyanin and flavonol metabolism in plant.